2020
DOI: 10.18632/oncotarget.27410
|View full text |Cite
|
Sign up to set email alerts
|

PDLIM4/RIL-mediated regulation of Src and malignant properties of breast cancer cells

Abstract: RIL/PDLIM4 gene was identified as a tumor suppressor, its expression is frequently altered in various types of malignancies. The product of RIL/PDLIM4 gene is an adapter protein involved in the actin cytoskeleton remolding and assembly of stress fibers crucial for cell motility and epithelial-mesenchymal transition. Although the exact mechanism tethering RIL to cancer development remains unknown some pieces of evidence suggest that RIL may act by suppressing activation of the protooncogene tyrosine-protein kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Yanyan Jia et al demonstrated downregulated expression of PDLIM4 promoted ovarian cancer cells migratory and invasion by activating STAT3 signal pathway, which contributed to lymph node metastasis in ovarian cancer (Jia et al 2019). However, the high level of PDLIM4 in the speci c breast cancer cell lines (MDA-MB-231 and MDA-MB-436) had a higher cell migratory rate via increasing Src kinase activity as an oncogene (Kravchenko et al 2020), demonstrating the controversial and diversity function of PDLIM4. In addition, PDLIM4 was proved to be highly expressed and underwent hypermethylation in THCA (Jiang et al 2023), but the biological effect on lymph node metastasis in PTC was still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Yanyan Jia et al demonstrated downregulated expression of PDLIM4 promoted ovarian cancer cells migratory and invasion by activating STAT3 signal pathway, which contributed to lymph node metastasis in ovarian cancer (Jia et al 2019). However, the high level of PDLIM4 in the speci c breast cancer cell lines (MDA-MB-231 and MDA-MB-436) had a higher cell migratory rate via increasing Src kinase activity as an oncogene (Kravchenko et al 2020), demonstrating the controversial and diversity function of PDLIM4. In addition, PDLIM4 was proved to be highly expressed and underwent hypermethylation in THCA (Jiang et al 2023), but the biological effect on lymph node metastasis in PTC was still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 , 32 ] PDLIM4, a gene which is frequently suppressed in various cancers, is considered as a tumor suppressor. [ 33 ] It has been shown that PDLIM4 expression is significantly decreased in ovarian cancer, which is related to the aggressive characteristics of this disease such as the proliferation, migration, and invasion abilities of cancer cells, leading to an inferior prognosis. [ 34 ] ELN is significantly differentially expressed between primary ovarian cancer and peritoneal metastatic ovarian cancers, indicating that ELN may be associated with the metastasis of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…COMP encodes the extracellular matrix glycoprotein, and its increased expression is implicated in the development of epithelial ovarian cancer involving in the proliferation, migration, invasion, and apoptosis of ovarian cancer cells regulated by SNHG25 [31,32] . PDLIM4, a gene which is frequently suppressed in various cancers, is considered as a tumor suppressor [33] . It has been shown that PDLIM4 expression is significantly decreased in ovarian cancer, which is related to the aggressive characteristics of this disease such as the proliferation, migration, and invasion abilities of cancer cells, leading to an inferior prognosis [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al found that PDLIM4 was highly methylated in tumor tissue by analyzing 38 pairs of patients with primary BC lymphatic metastases [129], and other studies showed that PDLIM4 expression was negatively correlated with tumor size, differentiation status, and SPF (S-phase fraction) value [130]. However, it has also been shown that upregulation of PDLIM4 expression promotes BC cell migration [131]. Proper assessment of its role in the malignant progression of BC facilitates the implementation of individualized tumor treatment.…”
Section: Pdlim4mentioning
confidence: 99%